The Effects of Vocational Education on Recidivism and Employment Among Individuals Released Before and During the COVID-19 Pandemic - McNeeley, Susan M. (International journal of offender therapy and comparative criminology, 2023)
Prior research shows employment is an important component of desistance, but there is mixed evidence regarding the effectiveness of prison-based education programs. Therefore, this study examines whether participation in vocational education programs while incarcerated improves recidivism and post-release employment outcomes. In addition, the study controls for the timing of release to examine whether recidivism and employment outcomes varied during the COVID-19 pandemic. Observable selection bias was reduced by using propensity score matching to create similar treatment and comparison groups. After matching, there were no differences in any outcome between those who obtained vocational certificates and the comparison group. The results demonstrate the importance of accounting for selection bias in evaluations of education and employment programs. It is recommended that career-focused educational programs incorporate the risk-needs-responsivity model and the continuum of care principle, build relationships with community employers, and assist with practical barriers to employment.